PROFIL TINEA KAPITIS DI POLI KESEHATAN KULIT DAN KELAMIN RSUD DELI SERDANG LUBUK PAKAM PADA TAHUN 2014 – 2017 - NURHALIMAH SIREGAR; FEBRINA D. PERTIWI (JURNAL ILMIAH SIMANTEK, 2020)
Dermatophytosis is a disease of tissue containing horn substances, such as the stratum corneum in the epidermis, hair andnails which causes the dermatophyte fungal group. Researcher interested to this study because there were no data in LubukPakam City before. To evaluate the profile of tinea capitis at Outpatient Clinic of Dermatology and Venerology Deli SerdangLubuk Pakam Hospital in 2014-2017. This study is descriptive with total sampling. Data used to describe the profile ofpatients with tinea capitis in Deli Serdang Lubuk Pakam Hospital in 2014-2017. The results of this study used UnivariatAnalysis test. Based on the results, this study revealed that the most patients from the classification, 12 patients (32,4%)were 1-10 years old. Based on the sex, 20 patients (54,1%) were men. Most patients lived in the village were 24 patients(64.9%). Based on the main complaints, 16 patients (43.2%) complained broken hair. Based on the medical record, therewere no data of history of contact on medical record. Based on the result, tinea capitis mostly occurred at 1-10 years old(32,4%), men (54,1%), lived in the village (64,9%), and with chief complaint broken hair (43,2%). There were no data ofhistory of contact on medical record.